Efeitos de nanopartículas de óxido de cobre (nano-cuo) e cloreto de cobre (cucl2) sobre a composição bioquímica e atividade fotossintética da Clorofícea Raphidocelis Subcapitata - Alho, Lays de Oliveira Gonçalves (2016)
Production and utilization of copper oxide nanoparticles (CuO-NP) have increased recently due to their specific physicochemical properties. Most of these nanoparticles end up in aquatic ecosystems, but their effects on the biota were not yet well characterized. The present study aimed to compare the toxicity of CuO-NP and copper chloride (CuCl2) in the microalgae Raphidocelis subcapitata, in order to determine whether the main cause of possible toxicity is due to released copper ions or intrinsic properties of the nanoparticle. We evaluated the effects of these two compounds on several physiological and biochemical parameters of the algae (photosynthetic activity, growth, dry weight, carbohydrates levels, total lipids content and lipid classes). Exponential growth phase algal cultures were exposed during 96 hours to different concentrations of CuO-NP (0.07 to 12.6 μM Cu L-1) and CuCl2 (0.07 to 2.29 μM Cu L-1). The mean inhibitory concentration for R. subcapitata exposed to nanoparticles at 96 h (IC50-96h) was 74 μM Cu L-1, while for CuCl2 was 0.65 μM Cu L-1. There was an increase in dry weight, total carbohydrates and total lipids in algae exposed to the highest copper concentrations in both treatments (salt and nanoparticles), but there was not much change in chlorophyll content after 96 hours of exposure. Concerning lipid composition, sterols (ST) and aliphatic alcohol (ALC) increased under CuCl2 exposure, while aliphatic hydrocarbons (HC) and triacylglycerols (TAG) increased in the presence of nano-CuO, compared to control. The highest concentrations of each compound reduced 36% of algae initial fluorescence (F0) and about 70% the maximum fluorescence (Fm) after 96 hours of metal exposure. Maximum (ɸM) and effective (ɸM ') quantum yields were affected by the two copper compounds, with the largest changes found in the algae exposed to nano-CuO. The major changes observed in the efficiency of oxygen complex evolution (F0/Fv) indicate that this was the main site of action of copper, through changes in the process of water photo-oxidation, especially in algae exposed to nano-CuO. The photochemical (qP) and non-photochemical quenching (qN) were not significantly altered by the metal. We found that CuCl2 was more toxic than nano-CuO in all parameters evaluated, and this can be related to lower free copper ions available in nanoparticles. In this study, we concluded that the two copper compounds significantly affect photosynthetic activity, of R. subcapitata, with more pronounced changes in algae treated with CuO-NP, which may indicate different forms of action between the dissolved copper in the salt and in the CuO-NP. The parameter F0/Fv showed greater sensitivity to copper, being potentially a good tool for research on the physiological stress generated by metals in microalgae.